2018
DOI: 10.1039/c7ta09913d
|View full text |Cite
|
Sign up to set email alerts
|

Hexagonal nanoplates of high-quality γ-gallium oxide: controlled synthesis and good heterogeneous catalytic performance for thiophenes

Abstract: Hexagonal nanoplates of high-quality γ-gallium oxide were successfully synthesized by using a competitive and cooperative interaction model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…25,26 For example, Wang et al prepared hexagonal nanoplates of high-quality gamma-gallium oxide (γ-Ga 2 O 3 ), which were further employed in ODS, and an excellent desulfurization performance was gained. 27 Our group reported the synthesis of oxygen-defective tungsten oxide and found that the variable valence induces a remarkably enhanced ODS activity. 28 Although numerous advantages of metal oxide catalysts have been achieved for ODS, an inevitable disadvantage is that the poor active-site exposure seriously limits the improvement of catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 For example, Wang et al prepared hexagonal nanoplates of high-quality gamma-gallium oxide (γ-Ga 2 O 3 ), which were further employed in ODS, and an excellent desulfurization performance was gained. 27 Our group reported the synthesis of oxygen-defective tungsten oxide and found that the variable valence induces a remarkably enhanced ODS activity. 28 Although numerous advantages of metal oxide catalysts have been achieved for ODS, an inevitable disadvantage is that the poor active-site exposure seriously limits the improvement of catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…22,25,26 Recently, we noticed that PVP could play a key role in forming high-quality g-Ga 2 O 3 nanostructures by its binding to gallium ions and gallium complexes, since this binding has contributed to the decrease of primary particle formation, nucleation and microstructural growth of g-Ga 2 O 3 in mild hydrothermal conditions. 19 This nding encourages the further use of this new method in the treatment of the formation of a-Fe 2 O 3 nanostructures.…”
Section: Introductionmentioning
confidence: 79%
“…Based on our recent work on analyzing various interactions including precipitate, coordination and binding equilibria in aqueous solution, 19 we consider that the contribution of PVP to the construction of nanoparticles of a-Fe 2 O 3 can be explained as the presence of the binding interaction between the PVP chain and the octahedral complex of Fe(II). The results of several independent experiments conrm this possibility.…”
Section: Formation Of the A-fe 2 O 3 -1mentioning
confidence: 99%
See 1 more Smart Citation
“…These can enhance the photocatalytic efficiency and stability of water splitting compared with bulk γ‐Ga 2 O 3 . [ 87 ] Other applications such as solar‐blind photodetectors [ 88 ] and heterogeneous catalytic performances for thiophenes [ 89 ] were also based on hydrothermally prepared γ‐Ga 2 O 3 .…”
Section: Group Iii–vimentioning
confidence: 99%